2006
DOI: 10.1088/0963-0252/16/1/024
|View full text |Cite
|
Sign up to set email alerts
|

Neutral gas density depletion due to neutral gas heating and pressure balance in an inductively coupled plasma

Abstract: The spatial distribution of neutral gas temperature and total pressure have been measured for pure N 2 , He/5%N 2 and Ar/5%N 2 in an inductively coupled plasma (ICP) reactor, and a significant rise in the neutral gas temperature has been observed. When thermal transpiration is used to correct total pressure measurements, the total pressure remains constant regardless of the plasma condition. Neutral pressure is depleted due to the pressure balance when the plasma pressure (mainly electron pressure) becomes com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…Finally, the neutral density has been recently obtained from the total neutral pressure measured by a manometer in combination with optical measurements of the rotational neutral temperature and significant neutral depletion was measured coincidental with neutral gas heating. 11 In this letter, we present measurements of neutral gas depletion obtained by direct measurement of the ground state neutral gas density. The neutral gas density ͑xenon atoms͒ is obtained by spatially resolved laser induced fluorescence spectroscopy with two-photon excitation ͑TALIF͒.…”
Section: Direct Measurements Of Neutral Density Depletion By Two-photmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the neutral density has been recently obtained from the total neutral pressure measured by a manometer in combination with optical measurements of the rotational neutral temperature and significant neutral depletion was measured coincidental with neutral gas heating. 11 In this letter, we present measurements of neutral gas depletion obtained by direct measurement of the ground state neutral gas density. The neutral gas density ͑xenon atoms͒ is obtained by spatially resolved laser induced fluorescence spectroscopy with two-photon excitation ͑TALIF͒.…”
Section: Direct Measurements Of Neutral Density Depletion By Two-photmentioning
confidence: 99%
“…A number of experimental studies in high density magnetized plasmas have suggested significant neutral gas heating with temperatures in agreement with the above estimate. 3,11,16 Secondly, one should incorporate the magnetic pressure in the overall pressure balance.…”
Section: Direct Measurements Of Neutral Density Depletion By Two-photmentioning
confidence: 99%
“…1 Direct measurements of neutral pressure with probes along the axis of an argon helicon plasma showed significant neutral depletion in the center of the discharge. 8 Additionally, computational simulations have been performed to model neutral transport and depletion. 3 Miljak et al observed a density maximum in a high-power, double-antenna helicon discharge attributed to neutral depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Gas heating is an important issue in the analysis of plasma behavior, and it has been studied elsewhere. 22,23 When an electron experiences the momentum transfer collision with a neutral atom, the electron losses only small amount of its kinetic energy in proportion to their mass ratio. Due to the light mass of helium, the helium gas is heated better by the electrons through the momentum transfer collision.…”
mentioning
confidence: 99%